One Size Does Not Fit All: Difficulties Applying the § 1331 “Substantial Question” Formula to § 1338 - Lovin, Kristen (Science and Technology Law Review, 2013)
Recent Federal Circuit case law has taken an aggressive stance towards establishing jurisdiction over state law claims, finding that questions concerning hypothetical patents are sufficiently “substantial” to warrant federal jurisdiction over quintessential state law issues. Several district courts and one Federal Circuit panel have challenged this approach as excessively expansive, encouraging a reimportation of 1331’s “substantial question” formulation into 1338. This paper argues that a direct importation of 1331 substantiality is not appropriate in the patent context because history does not require a direct import, policy considerations suggest that 1331 and 1338 jurisdiction differ in important ways, and direct importation raises several pragmatic concerns. Instead, an approach that draws from the original basis of 1338’s “substantial question of federal patent law” test and then incorporates selected aspects of 1331 substantiality is more appropriate.